2016
DOI: 10.5194/aab-59-201-2016
|View full text |Cite
|
Sign up to set email alerts
|

Physiological differences between twin and single-born lambs and kids during the first month of life

Abstract: Abstract. The effects of time after birth and of twinning on rectal temperature (RT), heart rate (HR), respiratory rate (RR) and body weight (BW) values were evaluated in five singleton Comisana lambs (three males and two females), five singleton Maltese Kids (three males and two females), four couples of twin Comisana lambs (four males and four females) and four couples of twin Maltese kids (four males and four females) during the first month of life. For all kids and lambs, RT, HR, RR and BW were recorded af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
2
8
2
Order By: Relevance
“…In the present study it can be observed that there is no difference related to gender and type of delivery. These results contradict the values mentioned by Fazio et al (2016), who did not find weight differences in the neonatal period in lambs born in twin deliveries (3.20±0.13 kg) and single deliveries (3.87±0.34 kg). Nobrega et al (2005) mention that the temperatures of the semi-arid region favor the survival of pups, but the inadequate nutritional level of the matrixes in the final third of pregnancy contributes to the occurrence of starvation/hypothermia as a consequence of the low weight at birth.…”
Section: Resultscontrasting
confidence: 99%
“…In the present study it can be observed that there is no difference related to gender and type of delivery. These results contradict the values mentioned by Fazio et al (2016), who did not find weight differences in the neonatal period in lambs born in twin deliveries (3.20±0.13 kg) and single deliveries (3.87±0.34 kg). Nobrega et al (2005) mention that the temperatures of the semi-arid region favor the survival of pups, but the inadequate nutritional level of the matrixes in the final third of pregnancy contributes to the occurrence of starvation/hypothermia as a consequence of the low weight at birth.…”
Section: Resultscontrasting
confidence: 99%
“…The moderate heritability (in the range h 2 = 0.33-0.77) of birth weight (Assan et al, 2002;Everett-Hincks et al, 2014) has been detected, and thus its importance in the selection process as one of the criteria employed has been confirmed. Birth weight is also influenced by external or internal factors, such as the year of birth (Gardner et al, 2007), the ewe's age (Thomson et al, 2004), the mature ewe's nutritional status (Kenyon et al, 2004(Kenyon et al, , 2014, litter size, or the sex of the lamb (Morris et al, 2003;Gootwine and Rozov, 2006;Schiller et al, 2015;Fazio et al, 2016). All of these factors also affect subsequent survivability traits and lambs' growth performance, as referred to by the abovementioned authors.…”
Section: Introductionmentioning
confidence: 99%
“…Stress and pain stimulate the sympathetic and parasympathetic nerves, and subsequently result in changes in clinical parameters such as body temperature, pulse rate, and respiratory rate (TPR) 10 which is usually absent in the similar studies and not much attention is paid to these changes together with cortisol. In addition to physiological and behavioral changes measurement 11,12 in animals to measure pain, serum cortisol levels can also be used. Cortisol is the main glucocorticoid hormone that is released in response to pain or stress.…”
Section: Introductionmentioning
confidence: 99%